Peran Psikologi dalam Memahami dan Memfasilitasi Mindset Gotong Royong di Desa Sembahe Kabupaten Deli Serdang - Tengku Nuranasmita; Anna Wati Dewi Purba; Sutrisno Sutrisno (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This community service program aims to revitalize the spirit of mutual cooperation (gotong royong) among the people of Sembahe Village, Deli Serdang, through a psychoeducational approach rooted in social psychology. The activity adopted a Participatory Action Research (PAR) method, emphasizing collaboration between program implementers and the community in identifying problems and designing solutions. The intervention was conducted through interactive lecture sessions exploring prosocial behavior, social norms, and group identity theory. Twenty participants, including local residents and village officials, actively engaged in discussions, shared experiences, and reflected on the declining practice of gotong royong. The results of the activity demonstrated an increased collective awareness of the importance of gotong royong, not only as a cultural heritage but also as part of social identity and community solidarity. The program successfully catalyzed behavioral change by fostering emotional and cognitive engagement with shared values. The commitment of village leaders to revitalizing communal activities reflects the positive impact of this intervention. These results demonstrate that psychology education can be a strategic tool for strengthening collective values and building social resilience in rural communities undergoing changes due to modernization.